Di Balik Konten Viral: Kebersyukuran dan Burnout Kreator TikTok - Haura Cantika; Karisma Riskinanti (Universitas Mercu Buana, 2026)
The rapid growth of the creator economy has increased the psychological demands experienced by digital content creators. This study aimed to examine the relationship between gratitude and burnout among TikTok content creators, both overall and across the three burnout dimensions: emotional exhaustion, depersonalization, and reduced personal accomplishment. A quantitative correlational design was employed involving 158 TikTok content creators selected through purposive sampling, a type of non-probability sampling. Data were collected using the Gratitude Questionnaire and the Maslach–Trisni Burnout Inventory (M-TBI). Spearman’s rho correlation analysis was conducted to examine the relationships between the variables. The results indicated that gratitude was not significantly associated with overall burnout (rs= −.015, p = .849). Likewise, no significant relationships were found between gratitude and emotional exhaustion (rs = −.079, p = .325) or reduced personal accomplishment (rs= −.096, p = .232). In contrast, gratitude was significantly and negatively associated with depersonalization (rs= −.492, p < .001), indicating a moderate relationship. These findings suggest that gratitude may help reduce tendencies toward depersonalization among TikTok content creators but does not appear to be associated with overall burnout or with the dimensions of emotional exhaustion and reduced personal accomplishment.